Helping abused and traumatized children : integrating directive and nondirective approaches - Gil, Eliana (Guilford Press, 2006)
Presenting an integrative model for treating traumatized children, this book combines play, art, and other expressive therapies with ideas and strategies drawn from cognitive-behavioral and family therapy. It demonstrates how to tailor treatment to the needs of each child by using both directive and nondirective approaches.